Douglas Steere and Elton Trueblood as Interpreters of John Woolman - Birkel, Michael L. (Quaker studies, 2023)
Douglas V. Steere and D. Elton Trueblood were among the most influential Quaker voices in the middle decades of the twentieth century among liberal and evangelical Friends, respectively. Each turned to John Woolman’s writings as inspiration for the needs of their times, from matters of spirituality and moral example to social justice and ecumenism.